Y – y1 = m(x – x1)
y-(-1)=-5(x-2)
Y+1=-5(x-2)
Answer:
Step-by-step explanation:
a + 143 = 180 {Linear pair}
a = 180 - 143
a = 37
37 + 93 + b = 180 {Angle sum property of triangle}
130 + b = 180
b = 180 - 130
b = 40
c + b = 90
c + 40 = 90
c = 90 - 40
c = 50
d + 120 = 180 {Linear pair}
d = 180 - 120
d = 60
? = 60 + 40 {Exterior angle property of triangle}
? = 100
She earns $825 more as a head buyer than a assistant buyer
Y = x^2 cos x
y' = x^2 * -sin x + cos x * 2x
= 2x cos x - x^2 sin x
= x ( 2 cos x - x sin x)
Yes
explanation : i took the test